Development of methods and algorithms for parameter estimation system of decarburization and combustible gas afterburning modes in an electric arc furnace - Eduard E. Merker; Victor A. Stepanov; Lyudmila N. Krakht; Alexander Yu. Kem (Advanced Engineering Research)
Introduction. Currently, in the Russian metallurgy, waste-gas heat under steelmaking in the electric arc furnace (EAF) is used inefficiently. This determines the urgency of the task to develop methods for СО to СО2 afterburning degree control under steelmaking in the EAF. Materials and Methods . A mathematical model of the decarburization and combustible gas afterburning modes under the reduced pellets electrosmelting at their continuous feed to the EAF bath is used to solve the problem. The proposed model allows estimating the mode parameters of the decarburization and combustible gas afterburning in the electric arc furnace. The role of the rate of carbon oxidation components in the common mode of decarburization and gas afterburning in the EAF is studied. Research Results . The possibility and efficiency of the CO afterburning by the oxygen beams in the counter gas flow system is experimentally confirmed. This allows accelerate the processes of metal heating and decarburization, as well as improve other technological parameters of the steel electrosmelting. Discussion and Conclusions . The mathematical modeling results show that a new method of supplying oxygen through the oxyfuel burners and the oxygen lance provides an increase in the energy efficiency of the steel electrosmelting in the electric arc furnace.